Optimal Recognition of Volleyball Player's Arm Movement Track Based on Embedded Microprocessor. (13th April 2022) - Liu, Ming; Wu, Jingtao; Tao, Jiangang
Abstract : An embedded microprocessor is the core part of the integrated circuit system, and it represents one of the highest levels of a digital integrated circuit design. Therefore, the design of low-power embedded microprocessors has become an important research direction in the integrated circuit design. Volleyball has always been a very important sport in our country, and it is a sport that the masses of people like to see. The basic techniques of volleyball include ready posture and movement, serving, hot ball, passing, smashing, and netting. The research content of this article is a simulation study of volleyball players' arm trajectory optimization recognition. In response to the above problems, this paper proposes an optimized recognition method based on the volleyball player's arm motion trajectory. The simulation results show that the method has high recognition accuracy and provides a strong scientific basis for improving the volleyball players' spike skills. Without interference from the right arm, the controller input and position tracking error will not fluctuate in 1 ≤ T ≤ 3, the controller input is stable, and the output error is zero. Based on the above simulation analysis, it can be seen that the control method does not require the robot kinematics and dynamics model to generate any regression matrix when designing the controller. The controller is suitable for the performance tracking of humanoid robot arms.